The sum if the geometric sequence given by:
an=-2(3)^(n-1)
will be:
when:
n=1
an=-2
when n=2
a2=-6
when n=3
a3=-18
when n=4
a4=-54
when n=5
a5=-162
when n=6
a6=-486
when n=7
a7=-1458
when n=8
a8=-4374
thus the summation of the term will be:
Sn=(-4374+-1458+-486+-162+-54+-18+-6+-2)
Sn=-6560
the answer is -6560
57. 8
58. 8
59. 24
60. 11.25 or 11
61. 20.52 or 21
62. 144
63. 7.37 or 7
64. 50%
65. 25%
66. 10%
67. 20%
68. 25%
hope this helped :)
Answer:
any number, n, multiplied by 1 is less than n + 1, so A = 1, B = any number
For example, 1 % 7. 1 * 7 = 7. 1 + 7 = 8
Also, having one of the variables be a decimal can make the numbers smaller.
For example, 28 * 0.5 = 14. 28 + 0.5 = 28.5